Fires Accidents and its Implication on Mechanical and Structural Properties of Different Construction Materials. Issue 1 (February 2021) - Aldefae, Asad H.; Edan, Abbas S.; Essa, Abbas F.
Abstract: In this paper, numerous and comprehensive physical and mechanical tests were carried out on various building construction materials (i.e. different kinds of floor and wall tiles, steel bars and widely used metal plate of doors and windows) to investigate how the high level of temperatures significantly impact on these materials through the physical, structural and mechanical changes. Before exposing of materials to this heating level, tests are performed on materials to be as a reference. The physical and mechanical characterization includes; compression tests, tensile tests, X-Ray Diffraction (XRD) as well as Field Emission Scanning Electron Microscope (FESEM). It was observed that the high temperature led to make damages on the internal and external structure of the materials and this obviously effects on the durability of the building or may lead to its destruction. It was noticed also that this level of temperature reduced the compressive strength whereas the molecular structure is strongly influenced by this reduction. Slightly changes in tensile strength of rebar were also noticed. High temperatures level are significantly effect on the internal structure of the floor and wall tiles and fine and moderate cracks on the roofs of these tiles are appeared and reduction in the modulus of rupture of the floor and wall tiles.